2014
DOI: 10.4081/jphia.2014.366
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing quality of life and predictors of low quality of life scores in patients on treatment for pulmonary tuberculosis: a cross sectional study.

Abstract: There is paucity of information on the quality of life of patients with pulmonary tuberculosis in Nigeria. This study assessed the factors influencing their quality of life and the independent predictors of low quality of life scores.Two hundred and sixty consecutive patients with pulmonary tuberculosis seen at the Lagos University Teaching Hospital were evaluated for health related quality of life using the World Health Organization Quality of life instrument (WHOQoL-BREF). Sociodemographic characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 11 publications
4
23
1
Order By: Relevance
“…It was found that aging had negative effect on the TB patients' physical well-being, with the younger patients having better physical well-being status than older patients. This result is congruent with other studies which published correlations between the quality of life among TB patients and demographic factors [10,13,[15][16][17]. In addition, this could be explicated based on the overall health status among individuals in older age group and possible existing co-morbidities among older population where illnesses such as hypertension and diabetes are more prominent.…”
Section: Discussionsupporting
confidence: 90%
“…It was found that aging had negative effect on the TB patients' physical well-being, with the younger patients having better physical well-being status than older patients. This result is congruent with other studies which published correlations between the quality of life among TB patients and demographic factors [10,13,[15][16][17]. In addition, this could be explicated based on the overall health status among individuals in older age group and possible existing co-morbidities among older population where illnesses such as hypertension and diabetes are more prominent.…”
Section: Discussionsupporting
confidence: 90%
“…Abilities are impaired by ill health and worse still chronic medical illnesses [68][69][70]. Quality of life can be altered by both the immediate and the long-term consequences of treatment especially the case of chronic illnesses [71][72][73][74][75][76][77][78]. Hence, the focus of medical practice has always been directed toward relieving physical symptoms of chronic medical diseases which often overlook the huge impact on the physical and psychological well-being, psychiatric comorbidity and the overall patient's quality of life.…”
Section: Quality Of Life and Well-being In Patients With Chronic Medimentioning
confidence: 99%
“…It has become important that tuberculosis and HIV control programs at public health clinics design strategies to improve the quality of health of tuberculosis and HIV separately or co-infected patients. Tuberculosis affected all predicted domains of QOL, including general health perceptions, somatic sensation, psychological health, spiritual wellbeing, and physical, social and role functioning [74][75][76]. Social stigmatization, isolation, pill burden, long duration of therapy, sexual dysfunction, loss of income and fear are associated with chronic medical diseases and all affect patients' QOL and well-being.…”
Section: Quality Of Life and Well-being In Patients With Chronic Medimentioning
confidence: 99%
“…It has become important that TB and HIV control programs as well as cancer awareness and prevention programs at public health clinics design strategies to improve the quality of health and life of these patients. In patients with chronic diseases, all predicted domains of quality of life (QOL), including general health perceptions, somatic sensation, psychological health, spiritual well-being, and physical, social, and role functioning, all tend to be negatively affected [86][87][88][89][90][91][92][93]. Social stigmatization, isolation, pill burden, long duration of therapy, sexual dysfunction, loss of income, and fear were additional specific problems related to chronic medical conditions [80,[82][83][84][85][86][87][88].…”
Section: Introductionmentioning
confidence: 99%
“…Social stigmatization, isolation, pill burden, long duration of therapy, sexual dysfunction, loss of income, and fear were additional specific problems related to chronic medical conditions [80,[82][83][84][85][86][87][88]. Despite available curative therapy, TB and its treatment still have significant short-and long-term consequences on patients' QOL [82,83,[86][87][88][89][90][91][92][93]. QOL has also been characterized as "the ultimate goal of all health interventions" [81].…”
Section: Introductionmentioning
confidence: 99%